The scholars involvement in dissemination of Malaysian architecture ideas from 1957 - 2004 - Kamarul Afizi Kosman ,; Abdul Halim Ismail,; Azimin Samsul Mohd Tazilan, (Penerbit UKM, 2008)
Success in developing an architectural identity does not depend solely on design experimentation but also on the effectiveness in disseminating the idea to society. The failure in developing Malaysian architectural identity was reportedly related to weaknesses in the process of disseminating the idea by its proponents. The success of Deutsche Werkbund Institution in the early 20th century, in promoting the identity of German society in various fields of endeavor including architecture was due to active involvement of its proponents in disseminating the ideology especially through publications. To see how far the lack of this factor (proponents’ involvement in disseminating ideas) contributed to development crisis of national architectural identity in Malaysia, a comprehensive study was done on 674 architectural writings produced in this country